2007
DOI: 10.1021/jf063446t
|View full text |Cite
|
Sign up to set email alerts
|

Curcuminoids, Curcumin, and Demethoxycurcumin Reduce Lead-Induced Memory Deficits in Male Wistar Rats

Abstract: This study investigated the neuroprotective effects of the curcuminoids against lead-induced neurotoxicity. The results show that lead significantly increases lipid peroxidation and reduces the viability of primary hippocampal neurons in culture. This lead-induced toxicity was significantly curtailed by the co-incubation of the neurons with the curcuminoids. In a whole animal experiment, rats were trained in a water maze and thereafter dosed with lead and/or curcumin (CURC), demethoxycurcumin (DMC), or bisdeme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
65
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 107 publications
(70 citation statements)
references
References 37 publications
5
65
0
Order By: Relevance
“…In vitro experiments also confirmed that curcumin inhibits AChE activity and has an IC 50 value of 67 µmol/L [54]. The strongest AChE inhibition was found using bisdemethoxycurcumin; a single dose of 30 µmol/L of bismethoxy curcumin, dimethoxy curcumin, or curcumin inhibits 85, 55, or 31% of AChE activity respectively [55]. Additionally, a molecular docking study shows curcumin interacts with actives site of AChE on amino acids (Tyr133, Glu202, Phe295, and Tyr337) to disrupt the activity of AChE [56].…”
Section: Discussionmentioning
confidence: 68%
“…In vitro experiments also confirmed that curcumin inhibits AChE activity and has an IC 50 value of 67 µmol/L [54]. The strongest AChE inhibition was found using bisdemethoxycurcumin; a single dose of 30 µmol/L of bismethoxy curcumin, dimethoxy curcumin, or curcumin inhibits 85, 55, or 31% of AChE activity respectively [55]. Additionally, a molecular docking study shows curcumin interacts with actives site of AChE on amino acids (Tyr133, Glu202, Phe295, and Tyr337) to disrupt the activity of AChE [56].…”
Section: Discussionmentioning
confidence: 68%
“…30 min after focal cerebral ischemia/ reperfusion in rats significantly diminished infarct volume, improved neurological deficit, decreased mortality, and reduced the water content of the brain [52]. Similarly, in another recent study, curcumin significantly inhibited heavy metal-induced neurotoxicity in rats [53].…”
Section: Animal Studiesmentioning
confidence: 64%
“…Curcumin protects PC12 cells against apoptosis induced by a lethal dose of H 2 O 2 and 1-methyl-4-phenylpiriinium ion (MPP ϩ )-induced apoptosis (73). Recent studies have suggested that curcumin significantly reduces metal-induced neurotoxicity in rat hippocampal neurons (74,75). It was proposed that the ability of curcumin to bind toxic metals and to form tight and inactive complexes could be a plausible pathway by which curcumin offers protection to the brain (76).…”
Section: Discussionmentioning
confidence: 99%